The idea of private law - Weinrib, Ernest Joseph (New York ; Oxford : Oxford University Press, 2013)
This revised edition of 'The Idea of Private Law' makes available one of the major works of modern legal theory. It includes a new introduction by the author, looking back at the work, its origins, and its aspirations.
Previous ed.: Cambridge, Mass.; London: Harvard University Press, 1995.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Keywords: Civil law -- Philosophy